2009
DOI: 10.1002/bit.22345
|View full text |Cite
|
Sign up to set email alerts
|

Sulfated membrane adsorbers for economic pseudo‐affinity capture of influenza virus particles

Abstract: Strategies to control outbreaks of influenza, a contagious respiratory tract disease, are focused mainly on prophylactic vaccinations in conjunction with antiviral medications. Currently, several mammalian cell culture-based influenza vaccine production processes are being established, such as the technologies introduced by Novartis Behring (Optaflu) or Baxter International Inc. (Celvapan). Downstream processing of influenza virus vaccines from cell culture supernatant can be performed by adsorbing virions ont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
53
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 42 publications
6
53
0
Order By: Relevance
“…1A) adsorbed to the weak cation exchanger C75-MA and was desorbed by an increased ionic strength via NaCl. A similar result, even more pronounced, was described by Opitz et al (2009) for purification of cell culture-derived influenza virus particles. The overall pI of influenza virus particles as judged by the subtype A 2 /Singapore/57 (5.0; Zhilinskaya et al, 1972) is less acidic than the pI of Vaccinia virus particles.…”
Section: Separation Of Mva-bnsupporting
confidence: 76%
See 4 more Smart Citations
“…1A) adsorbed to the weak cation exchanger C75-MA and was desorbed by an increased ionic strength via NaCl. A similar result, even more pronounced, was described by Opitz et al (2009) for purification of cell culture-derived influenza virus particles. The overall pI of influenza virus particles as judged by the subtype A 2 /Singapore/57 (5.0; Zhilinskaya et al, 1972) is less acidic than the pI of Vaccinia virus particles.…”
Section: Separation Of Mva-bnsupporting
confidence: 76%
“…Several studies reported antiviral activities of sulfated cellulose and sulfated dextran/dextrines (Baba et al, 1988;Chattopadhyay et al, 2008;Mitsuya et al, 1988;Piret et al, 2000) as well as the binding of virus particles to Cellufine 1 sulfate (O'Neil and Balkovic, 1993;Opitz et al, 2009). Although the precise interaction between these viruses and sulfated cellulose is currently not fully understood, it represents a potential alternative to heparin and heparan sulfate as ligand for MVA-BN 1 virus particles.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations